1973
DOI: 10.1159/000259818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rate of Gland Function on Parotid Saliva Fluoride Concentration in the Human

Abstract: A series of experiments were carried out to determine the effect of the rate of gland function on parotid saliva fluoride levels in the human. Means for fluoride for stimulated parotid saliva ranged from 0.012 to 0.02 ppm. These are much lower levels than those previously reported for whole saliva and support other electrode analyses recently reported. In a 3-hour experiment involving continuous exogenous stimulation, salivary fluoride levels showed no alterations suggestive of depletion. Significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1975
1975
1994
1994

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Similar low parotid salivary fluoride lev els were found by Shannon et al [1973] in stimulated samples. However, in unstimu lated samples, they found higher values (approx.…”
Section: F In Salivasupporting
confidence: 79%
“…Similar low parotid salivary fluoride lev els were found by Shannon et al [1973] in stimulated samples. However, in unstimu lated samples, they found higher values (approx.…”
Section: F In Salivasupporting
confidence: 79%
“…The salivary fluoride concentration is independent of salivary flow rate (Shannon et aL, 1973;Shannon, 1977;Oliveby et aL, 1989a,b,c). Ingested fluoride doses of 3,5, and 10 mg increase the fluoride concentration to a peak level in parotid saliva within 30-40 min after fluoride intake (Shannon and Edmonds, 1972).…”
Section: Fluoridementioning
confidence: 99%
“…2 We suggested that the reason for the lack of change in stimulated saliva is probably that the F ion is carried passively in bulk flow with the fluid of secretion. Furthermore, the presence of a higher concentration of F in unstimulated saliva probably results from a proportionate reabsorption of sodium and water,,thus, producing an apparent increase in the F level which is indeed induced simply by the concentrating effect of water removal.…”
Section: Discussionmentioning
confidence: 98%
“…'2 The level in unstimulated parotid saliva is slightly, but significantly, higher than that found in stimulated fluid. 2 Orally administered doses of F larger than 1.0 mg induce virtually immediate increases in the F level in stimulated parotid saliva.1,3 Peak concentration is usually reached 30 to 50 minutes after administration and, although the subsequent decline is relatively sharp, a significant elevation in the F level is sustained for at least four hours. 3 A caries-protective function has not been established for the F present in saliva.…”
mentioning
confidence: 99%